Asbuton Pracampur Antara Harapan dan Kenyataan - H. R. Anwar Yamin; Willy Pravianto -; Hikma Dewita - (Jurnal Ilmiah Poli Rekayasa, 2014)
Preblended asbuton is one of a kind bitumen modification that used in Indonesia. From the results of laboratory tests and field trials scale, obtained that paved using asphalt mixture has better technical properties than conventional asphalt mix made bu asphalt Pen 60. Therefore, in the General Specifications of Highways 2011, this type of asphalt used for dense and  heavy trafficed road. Although the long-term performance of asphaltic mixtures  using preblended asbuton have not been surely known, but until now there has been a lot of road sections in Indonesia have used it. The purpose of this study was to evaluate the long-term field performance of preblended asbuton asphaltic mixtures. To achieve these objectives, filed conditions survey, testing and sampling tests have conducted on several roads that use different preblended asbuton (further named Code-O and Code-B), which has served the traffic from one to three years. In this study, the filed long-term performance of the preblended asbuton asphaltic layer  viewed from the level of damage and aging asphalt development that occurs in the field. Some conclution derived from this study were that preblended asbuton Code-O or Code-B has a good rutting resistance but preblended asbuton Code-B has a better cracking resistance than  Code-O. In terms of short-term aging point of view, preblended asbuton Code-O are better than asphalt Pen 60 and contrary to the Code-B, but for long-term the aging resistance either of preblended asbuton Code-O  or Code-B was relative similar to asphalt Pen 60.